Acrílico auto-polimerizável associado ou não a retalho mucoperiostal simples, no tratamento de fístula oronasal experimental, em cães - Goelzer, Luciana Prati (2002)
Oronasal fistula in dogs may determine secondary complications, that need surgical treatment. Repair of oronasal fistula constitute a challenge to surgeons. In order to evaluate the efficacy of polymethylmethacrylate with or without a mucoperiosteal single flap in the treatment of experimental oronasal fistula of canine teeth, in 12 dogs, an experimental model is presented. The dogs were observed for 60day period, with clinical, histhological and radiological evaluation. Recurrence was observed in three fistulas (12,5%) and the acrylic was exposed. Partial suture failure happened in eight flaps (66,6%) and total suture failure happened in one flap (8,3%). The histhopathologic analysis after 60 postoperative days showed evidence of chronic inflammatory reaction progressively lesser than 30 days of evaluation. In the radiographic evaluation was observed fracture consolidation adjacent to the acrylic. The experimental model is appropriate to study the repair of oronasal fistula in dogs. The polymethylmethacrylate is efficient for the repair of experimental oronasal fistula, without evidence of rejection, and it can be utilized associated or not to a mucoperiosteal single flap. The use of flap improves the healing process.